Autobiographical recall as a tool to enhance the sense of self in Alzheimer's disease. (May 2019) - El Haj, Mohamad; Gallouj, Karim; Antoine, Pascal
Highlights: We invited AD patients to describe themselves after autobiographical retrieval. High self-description was observed after autobiographical retrieval. Autobiographical retrieval alleviates the diminished sense of self in AD. Abstract: We investigated whether autobiographical retrieval would improve the sense of self in Alzheimer's disease (AD). Participants with AD and controls were asked to produce statements describing their self, i.e., statements to the question "Who am I?", after two conditions: after autobiographical retrieval and after a control verbal fluency task. The production of "Who am I?" statements was analyzed regarding three self-dimensions (i.e., physical self, social self, and psychological self). Results revealed better production of descriptions related to physical self, social self, and psychological self after autobiographical retrieval than after the control condition in AD patients and control participants. At a clinical level, encouraging patients to retrieve autobiographical memories may be used as a tool to activate the sense of self in AD. At a theoretical level, they are concordant with a model suggesting a bidirectional relationship between autobiographical memory and the self in AD.